The Effect of Learning Environment and Vocabulary Mastery on Chinese Speaking Skills - Thamrin, Lily; Suhardi, Suhardi (FKIP Universitas Lampung, 2022)
The Effect of Learning Environment and Vocabulary Mastery on Chinese Speaking Skill. Communication is considered one of the human needs, which is pivotal in social interaction. In communicating, the use of language is necessary to understand each other. For students of the Chinese Language Education Department, Universitas Tanjungpura, Indonesia speaking Chinese is encouraged. However, low levels of Chinese speaking skills become the obstacles to speaking the language. In addition, the lack of discipline in learning the language and mastery of Chinese vocabulary were the main problems that students have. Therefore, it was necessary to conduct research on vocabulary mastery and students' Chinese speaking skills. This research employed a qualitative descriptive method and a questionnaire with a Likert scale calculation as a data collection method. The data processing and data analysis used a qualitative interactive model consisting of three stages; data reduction, data display, and conclusion drawing and verification. The results revealed that the students' Chinese language skills were still very low. The highest score of HSK was at intermediate level 3 with a percentage of 25% and intermediate level 4 with a percentage of 43%. For HSKK speaking skills, students' skills were only at the basic level of 44% and 56%. From this research, it can be concluded that the low ability of students to speak Chinese was the result of the influence of the internal and external factors of students where the discipline of using the language was still very low. Furthermore, the influence of the family and community environment was also one of the factors that greatly affected students' learning. Keywords: learning environment’s influence, vocabulary mastery, chinese speaking skills.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202218